2009
DOI: 10.1530/eje-08-0642
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum adiponectin levels versus bone mineral density, bone metabolic markers, and vertebral fractures in type 2 diabetes mellitus

Abstract: Background: Although, adiponectin might be associated with bone metabolism, the relationships between serum adiponectin and bone mineral density (BMD) as well as vertebral fracture in type 2 diabetes are still unclear. Objective and methods: We investigated the relationships between each of serum total and high molecular weight (HMW) adiponectin versus BMD, bone markers, and the presence of vertebral fractures in a total of 231 men and 170 post-menopausal women with type 2 diabetes. Results: Multiple regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 45 publications
1
64
1
4
Order By: Relevance
“…Two other studies have shown a significant association between vertebral fracture and adiponectin in men. (17,23) In contrast, Michaelsson and colleagues (26) could not demonstrate a significant association after an extended follow-up of 15 years. Thus far no studies have shown a relationship between adiponectin and fracture risk in women.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Two other studies have shown a significant association between vertebral fracture and adiponectin in men. (17,23) In contrast, Michaelsson and colleagues (26) could not demonstrate a significant association after an extended follow-up of 15 years. Thus far no studies have shown a relationship between adiponectin and fracture risk in women.…”
Section: Discussionmentioning
confidence: 87%
“…In the present study, serum adiponectin was inversely correlated to BMD at any site as found in other studies. (17,23,25,26) After adjustment for total hip BMD, the association between serum adiponectin persisted although the GR was somewhat decreased (1.33; 95% CI, 1.12-1.58). These data suggest that adiponectin has almost the same predictive value as BMD, and is only in part dependent on BMD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This undercarboxylated osteocalcin was shown to stimulate pancreatic β-cell proliferation and insulin secretion via embryonic stemcell phosphatase expressed in osteoblast and thus positively modulate energy metabolism (Kanazawa et al 2009, Karsenty & Ferron 2012.…”
Section: Calcitriol As a Mediator For All Three Tissuesmentioning
confidence: 99%